Analysis of The Effect of Bank Capacitor Placement as Voltage Drop Increase in Distribution Network - Rofandy, Muhammad Yudha; Hasibuan, Arnawan; Rosdiana, Rosdiana (LPPM Universitas Andalas, 2022)
The quality of electricity distribution in the distribution network is an important thing that must be considered. To maintain the quality of electrical energy, there are several parameters that must be considered in the distribution network, including voltage drop, power losses, power factor and other factors. One of the solutions used to improve the voltage drop and power factor is to install a capacitor bank in the distribution network. This paper will discuss the placement of capacitor banks using the fuzzy logic method with inputs in the form of voltage profiles, power losses and power flow calculations using ETAP 12.6.0 software. In the Rao feeder, the final voltage is 16.806 kV or has passed the standard set by PLN (-10% and +5%). The Rao feeder has a power loss of 0.242 MW and a power factor of 0.7815. Fuzzy logic method is used to determine the optimal location of capacitor placement. After the installation of the capacitor bank, the terminal voltage increases and the total power loss decreases, while the power factor increases. From the results obtained, PLN as a supplier of electrical energy can reduce power losses by placing and installing capacitor banks in the distribution network.